Internalization of Character Values through the Backpacker Program in Sekolah Menengah Pertama Islam Terpadu Al-Ibrah Gresik - Suradji, Muchamad; In’am, Akhsanul; Faridi, Faridi; Khozin, Khozin (International Journal of Education, Culture, and Society, 2025)
This research aims to describe the internalization of character values ​​through the backpacker program. This research uses a constructivism paradigm with a qualitative approach. The data collection techniques in this research include observation, interviews and documentation. The data analysis technique uses three steps that must be carried out, namely condensing the data, presenting the data, and drawing conclusions/verification. The results of research related to the internalization of character values ​​through the backpacker program at Sekolah Menengah Pertama Islam Terpadu (SMPIT) Al-Ibrah are going well. This can be seen from the backpacker program completion aspect, all students have completed 7 indicators starting from (1) Students can develop a spirit of independence, (2) Students can develop problem-solving skills, (3) Students can develop communication skills with the community, (4) Students can develop a spirit of brotherhood and solidarity in group work, (5) Students can train physical resilience and emotional resistance to problems, (6) Students can develop a love of their homeland, (7) Students can develop a spirit of empathy and caring. This program provides space for them to learn from real experiences, hone social skills, and strengthen moral values ​​that are useful for their future lives.